Pemanfaatan Facebook Ads Bagi Pelaku UMKM dalam Pemasaran Produk - Suryadi, Sudi; Nur Siagian, Taufiqqurahman; Kurniawan Nst, Mhd.Bobbi (Jurnal Mitra Pengabdian Farmasi, 2022)
MSME actors in marketing their products conventionally and have not done product marketing through digital marketing. This community service activity aims to: 1) provide insight into the concept of digital marketing and technological products used for product marketing, 2) provide training and simulations on the use of digital media in product marketing, 3) compose effective persuasive messages, and 4 ) provide solutions to realize MSME actors to promote products through digital media. Service activities are carried out using the FGD method, training and mentoring. In general, community service activities went well and could increase public knowledge from an average value of 7 to 9 or an increase of 23.26%. This training and mentoring activity is very good and right on target. From this activity, the community began to 1) understand the concept of digital marketing and technological products that can be used for marketing MSME products, 2) train and simulate the marketing of MSME products using digital media such as Facebook ads.